The so-called relation forms of nouns in South Saami: A byproduct or remnant of Uralic *-mpV? - Ylikoski, Jussi (Finnisch-Ugrische Forschungen, 2019)
The paper describes a previously little-known grammatical category in South Saami. Termed here as “relation forms”, the phenomenon in question is etymologically related to the comparative and superlative marking of adjectives, but synchronically quite distinct from it. The suffix -be/-åbpoe can be attached to not only adjectives (e.g., nuerebe ‘younger’, båarasåbpoe ‘older’), but also to nouns and kinship terms in particular (e.g., tjidtjebe ‘(the) mother’, vuanavåbpoe ‘(the) mother-in-law’), and the superlative marker -mes/-ommes can be used similarly, albeit to a lesser extent. The paper discusses the position of such forms in South Saami morphology, syntax and sentential semantics, especially in relation to markers of definiteness and possession. From a diachronic perspective, South Saami sheds new light on the origin of the Saami-Finnic (and Hungarian) comparative marker *-mpV, and from a typological point of view, it is proposed that the closest analogues to the Saami phenomenon can be found in Tungusic, which also adds to our understanding of the development of *-mpV comparatives – possibly from a more original contrastive function of the suffix.